Development of WebGIS for Street Light Mapping Using Geospatial Tools - Anisya, Anisya; Fajrin, Fajrin; warman, Indra; Minarni, Minarni; Syahrani, Anna; Nugroho, Fajar (Informatika, Universitas Jenderal Soedirman, 2025)
Padang City, as one of the cities the largest on the west coast of Sumatra Island, plays a strategic role in the economy and government. One of the vital infrastructures that supports public activities is the street lighting system. However, the monitoring and maintenance of streetlights still face obstacles, especially in North Padang District, which is the busiest area due to the presence of numerous educational facilities, government offices, and economic centers. This research aims to develop a WebGIS application that facilitates the monitoring and management of street lighting more efficiently. Our research contributes by introducing a new approach to spatial-based streetlight management strategies. This approach is based on a methodology for field data collection and spatial database development to manage all stages of streetlight infrastructure management. This application integrates geospatial technology by utilizing GeoServer, QGIS, and PostgreSQL for visualization and spatial data management. With this system, information about the location and condition of streetlights can be accessed in real-time, thereby facilitating better planning and maintenance of street lighting infrastructure. The result of this study is a WebGIS application capable of mapping and monitoring streetlight points interactively. The implementation of this system is expected to assist relevant authorities in improving the effectiveness of street lighting management in Padang City and contribute to the development of geospatial technology-based solutions for urban infrastructure.